Centro comunitario municipal del Rímac - Becerra Posito, Greyci Gianella (2022)
Converting the property of a military barracks that was originally located on the outskirts of the city of Lima, will provide this area with important green areas, facilities, and housing, as well as connect it with the fragile ecosystem on the adjacent slopes. This Community Centre will provide various facilities to the residents of neighboring areas, located next to an important central public space that will allow the community to gather for celebrations of various kinds. It is conceived an intermediary between the frontal public space and another open space, more intimate one that will support activities aimed at children. These space of the main entrance very illuminated, have been conceived as the space of interrelation and integration of the assistants, it will be a place for people to recognize each other, meet, dialogue, and access the different workspaces. The building is formulated with a frame structure with concrete columns and metal beams, and its materials have been chosen for their good thermal behavior. The project will incorporate the technology of converting the energy generated by passers-by when they step on the receivers located on the floor and will convert into electrical energy to be used in the movement of the "brise-soleil" located on the facade. Likewise, the Community Centre has flexible environments since it will serve as a refuge in emergency situations.